Green's Function Approach for Late-Time Tail and Echoes in Damour–Solodukhin Type Wormholes - Qian, Wei-Liang [UNESP]; Pan, Qiyuan; Li, Guan-Ru [UNESP]; Guo, Hong; Lin, Kai; Yue, Rui-Hong (Wiley, 2024)
This study elaborates on two distinctive features in Damour–Solodukhin wormhole's waveforms: late-time tails and echoes. As a well-known black hole mimicker, these characteristics are crucial in differentiating wormholes from classical black holes. They emerge in the final phases of quasinormal oscillations and arise from specific structures in the Green's function. The late-time tail results from branch cut contributions, indicating a need to refine our interpretation of spacetime geometry. The echoes originate from additional quasinormal modes, similar to scenarios with metric discontinuities. These observations suggest that late-time wave behavior could be a unique signature of wormholes. Furthermore, the study hints at a possible interaction between late-time tails and echoes in the waveform's evolution.
Keywords: echoes; Green's function; late-time tail; quasinormal modes; wormhole